1992
DOI: 10.1091/mbc.3.7.735
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions in the Dictyostelium G alpha subunit G alpha 2 produce dominant negative phenotypes and inhibit the activation of adenylyl cyclase, guanylyl cyclase, and phospholipase C.

Abstract: Previous studies have demonstrated that the Dictyostelium Ga subunit Ga2 is essential for the cAMP-activation of adenylyl cyclase and guanylyl cyclase and that ga2 null mutants do not aggregate. In this manuscript, we extend the analysis of the function of Ga2 in regulating downstream effectors by examining the in vivo developmental and physiological phenotypes of both wild-type and ga2 null cells carrying a series of mutant Ga2 subunits expressed from the cloned Ga2 promoter. Our results show that wild-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 61 publications
0
52
0
Order By: Relevance
“…Furthermore, whereas cAMP-mediated increases in cAMP in vivo require Go,2, in vitro GTP~/S activation of adenylyl cyclase is uninhibited in all of the g~-cell lines (Pupillo et al 1992 and unpubl.). This latter result could be explained if B~/stimulated the enzyme (Okaichi et al 1992;PupiUo et al 1992). In vivo, excitation of cAR1 would cause the release of B~/from G~2, whereas in vitro GTP~/S would cause release of B~/ from any other G-protein.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, whereas cAMP-mediated increases in cAMP in vivo require Go,2, in vitro GTP~/S activation of adenylyl cyclase is uninhibited in all of the g~-cell lines (Pupillo et al 1992 and unpubl.). This latter result could be explained if B~/stimulated the enzyme (Okaichi et al 1992;PupiUo et al 1992). In vivo, excitation of cAR1 would cause the release of B~/from G~2, whereas in vitro GTP~/S would cause release of B~/ from any other G-protein.…”
Section: Discussionmentioning
confidence: 96%
“…Cyclic AMP mass assays were performed as published previously (29). Cells were starved for 0.5 h in phosphate buffer, washed, resuspended, and then stimulated with 50 M folic acid, and accumulated cAMP was measured using the Cayman cAMP enzyme immunoassay (Cayman Chemical Co., Ann Arbor, MI) according to the manufacturer's protocol.…”
Section: Purification Of His 6 -Tagged Erk2 Protein By Ni 2ϩmentioning
confidence: 99%
“…Guanylyl cyclase is stimulated by the receptor (Mato and Malchow, 1978). Previous studies have indicated that adaptation of the cGMP response occurs upstream of guanylyl cyclase (Van Haastert, 1983a), presumably at the receptor or at the Ga2-protein (Okaichi et al, 1992). Detailed kinetic studies of cAMP binding to D. discoideum cells suggest that a subpopulation of surface receptors is involved in the activation of guanylyl cyclase and that adaptation is associated at the interconversions between active and inactive receptor forms (Van Haastert et al, 1986).…”
Section: Introductionmentioning
confidence: 99%